Pengaruh Service Quality, Price Dan Customer Satisfaction Terhadap Repurchase Intention Di AMS Bengkel Kota Malang. - Muzhaffirah, Tarishah Abidah; Farida, Eka; Athia, Ita (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research aims to analyze the effect of service quality, price, and customer satisfaction on repurchase intention at AMS Bengkel in Malang City. The research adopts a quantitative approach with an explanatory research design. Primary data were collected through questionnaires distributed to 110 respondents who are active customers of AMS Bengkel. The data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results show that service quality, price, and customer satisfaction simultaneously have a significant effect on repurchase intention. However, partially, only service quality and price have a significant influence, while customer satisfaction does not significantly affect repurchase intention. Thus, service quality and price are the main factors driving customers’ repurchase intention at AMS Bengkel Malang. These findings contribute to the development of marketing strategies in the automotive service sector, particularly in formulating policies focused on increasing customer satisfaction and loyalty to remain competitive in the automotive workshop industry. This study may also serve as a reference for future research with a similar focus. Keywords: Service Quality, Price, Customer Satisfaction, Repurchase Intention, Automotive Services Pendahuluan